PERANAN LEMBAGA ADVOKASI ANAK (LADA) DALAM MENDAMPINGI KORBAN EKSPLOITASI SEKSUAL KOMERSIAL ANAK DI BANDAR LAMPUNG (Studi Pada Lembaga Advokasi Anak (LAdA)) - Susanty, Elfira; Fatimaningsih, Endry (SOCIOLOGIE, 2013)
Commercial sexual exploitation of children (CSEC) constitutes a violation of childrens rights. Violations committed by placing children as sexual commodities for the benefit of some parties. The commercial sexual exploitation of children has negative impacts which are in the form of physical, psychological and negative stigma in society. In dealing with the risk of violence, children as unstable souls human being need companion so that is why The Institute for Child Advocacy (LAdA) as the NGOs that have been concerned with the issue of various exploitation of children have a specific strategy in assisting child victims of commercial sexual exploitation. This research aims to clarify the role of Children Advocacy Institute (LAdA) in assisting child victims of commercial sexual exploitation in Bandar Lampung. This research was qualitative research and process of determining the informants based on purposively technique chosen. The method of data collection was conducted using interviews and documentation. The data analysis was done by data reduction, data display, and conclusion. Based on the research conducted, the obtained results of the study, there are two forms of assistance made by LAdA, the assessment or litigation (law) which is based on Law no. 23 of 2002 Section 83, about Protection of Children and Non-litigation counseling in the form of psychological and sociological done continuously to provide reinforcement to both the victim and the victims family as well as the provisioning of education that aims to leave the profession CSEC victims as perpetrators of child prostitution and have a better future.Keywords: Commercial sexual, exploitation, role